The future is urban : an urban bioethics perspective - Tai, Michael Cheng-Teh (Array, 2020)
This paper proposes a future urban that is bioethically viable not only in hardware construction but also in software equipment supporting the hardware’s viability for a harmonious relationship between humankind and nature. The future urban must not develop to become only a gathering of people in the city but ought to be designed to integrate within the global ecosystem. This paper will suggest a list of basic infrastructural requirements for an ecologically sustainable future urban. The methodology used in this paper is qualitative descriptive, derived from paper’s literature reviews along with other scholars who provided insight for the author to develop a list of recommendations for future urban planning.